1993
DOI: 10.1007/bf01182928
|View full text |Cite
|
Sign up to set email alerts
|

The stimulating influence of the raph� nuclei on the morphofunctional development of the hippocampus during their combined cultivation

Abstract: It has been demonstrated in combined (raphé nuclei-hippocampus, cerebellum-hippocampus) organotypical cultures of the brain of newborn rats that, unlike cerebellar explants, the raphé nuclei grow in an oriented manner toward the hippocampus and exert a stimulating influence on its morphofunctional development; this is manifested: a) in an intense proliferation and migration of glial cells, which are accompanied by accelerated growth of neuronal processes and an increase in the dimensions of the initial piece; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…Besides, PF 4 is released in combination at the site of injury or endothelial inflammation, even affect greater than described experimentally likely to occur in vivo [37]. 5-HT and PF 4 are widely recognized as activation symbols in lots of research [38,39]. Serotonin exists in hippocampus, frontal neocortex and platelets, being stored in subcellular storage vesicles at the terminal branches of neurons.…”
Section: Discussionmentioning
confidence: 96%
“…Besides, PF 4 is released in combination at the site of injury or endothelial inflammation, even affect greater than described experimentally likely to occur in vivo [37]. 5-HT and PF 4 are widely recognized as activation symbols in lots of research [38,39]. Serotonin exists in hippocampus, frontal neocortex and platelets, being stored in subcellular storage vesicles at the terminal branches of neurons.…”
Section: Discussionmentioning
confidence: 96%
“…More study is therefore needed to elucidate this issue. Chubakov et al (1993) demonstrated that the serotoninergic influences of the raphe nuclei were important for the morphofunctional development of the hippocampus.…”
Section: Discussionmentioning
confidence: 98%
“…Serotonin (5-HT), like other monoamine neurotransmitters, has been shown to play a role in regulating brain development before the time it assumes its role as a neurotransmitter in the mature brain (Chubakov et al, 1986(Chubakov et al, , 1993Lauder, 1990;Whitaker-Azmitia, 1991;Turlejski, 1996;Whitaker-Azmitia et al, 1996). This neurotransmitter is concentrated in the raphe nucleus of the brain, and is also present in platelets.…”
Section: Dopamine Involvement In Emotional Status and Learningmentioning
confidence: 99%